2020
DOI: 10.3389/fonc.2020.532292
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Birinapant, a SMAC Mimetic Compound, Alone or in Combination in NSCLCs With Different Mutations

Abstract: Liver kinase B1 (LKB1/STK11) is the second tumor suppressor gene most frequently mutated in non-small-cell lung cancer (NSCLC) and its activity is impaired in about half KRAS-mutated NSCLCs. Nowadays, no effective therapies are available for patients having these mutations. To highlight new vulnerabilities of this subgroup of tumors exploitable to design specific therapies we screened an US FDA-approved drug library using an isogenic system of wild-type (WT) or deleted LKB1. Among eight hit compounds, Birinapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…[1][2][3][4] Furthermore, we reported that the introduction of KRASmutant isoforms in H1299 cell line triggered a metabolic reprogramming different from that observed in the KRAS WT cell line, 5 which in turn differently influenced cell metabolic responses to treatments 6 and nutrient addiction. 7 In most of the manuscripts cited previously and in other contexts, 8,9 we also reported that KRAS-mutant clones derived from H1299 cell line had similar features of the endogenously mutated KRAS NSCLC cell lines.…”
Section: Mir-17 Epigenetic Modulation Of Lkb1 Expression In Tumor Cel...mentioning
confidence: 58%
“…[1][2][3][4] Furthermore, we reported that the introduction of KRASmutant isoforms in H1299 cell line triggered a metabolic reprogramming different from that observed in the KRAS WT cell line, 5 which in turn differently influenced cell metabolic responses to treatments 6 and nutrient addiction. 7 In most of the manuscripts cited previously and in other contexts, 8,9 we also reported that KRAS-mutant clones derived from H1299 cell line had similar features of the endogenously mutated KRAS NSCLC cell lines.…”
Section: Mir-17 Epigenetic Modulation Of Lkb1 Expression In Tumor Cel...mentioning
confidence: 58%
“…Colombo et al have evaluated the anticancer effect of birinapant (apoptosis inhibitor) and ralimetinib (p38 inhibitor) in the liver kinase B1 deleted clone and RAS muted cell lines and the outcome showed restoration of kinase activity (Colombo et al, 2020 ). In another study by Mortensen et al, the combination of onalespib and cisplatin significantly increased the antiproliferative, pro apoptotic, and antimigratory effect (Mortensen et al, 2020 ).…”
Section: Oncotherapeutics For the Management And Treatment Of Cancermentioning
confidence: 99%
“…Whilst this approach has been employed extensively to investigate TNF-induced inflammation [ 18 , 23 , 31 33 ], and to some extent TNF-induced cell death [ 34 36 ], the role of TNF/TNFR1 signalling pathway crosstalk in guiding cell-fate decisions in single cells has been understudied. It is vital to understand the mechanisms driving cell-to-cell variability in response to TNF and modulators of the TNF/TNFR1 signalling pathway, as drugs designed to promote TNF-induced cell death suffer from fractional killing [ 37 40 ], and poor responses in various cell lines [ 39 , 41 ].…”
Section: Introductionmentioning
confidence: 99%